Role of permafrost thaw transitions in biogeochemical nitrogen cycling - Merritt N. Logan; Monique S. Patzner; Jacob P. VanderRoest; Bridget B. McGivern; Nivetha Srikanthan; Myrna J. Simpson; Amy M. McKenna; Kelly C. Wrighton; Casey Bryce; Andreas Kappler; Thomas Borch (Soil & Environmental Health)
Significant organic nitrogen (ON) stocks have accumulated in permafrost peatlands over millennia. Climate change is expected to increase peatland thaw, making this ON more susceptible to biogeochemical degradation. However, the interplay between thaw-released N and N cycling remains poorly understood. To elucidate ON composition across a thaw transition (palsa to thaw front to bog), we employed 21 ​T electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) and nuclear magnetic resonance (NMR) spectroscopy. In addition, we performed metatranscriptomic sequencing to evaluate microbial activity changes in N cycling pathways between the palsa and bog. We observed an approximate 10-fold increase in dissolved ON and a significant rise in ammonium concentration between the palsa and thaw front. Additionally, there was a reduction in the peptide-like fraction and an increase in the aromatic fraction of dissolved ON molecules. Dissolved ON concentrations decreased by 73 ​% between the thaw front and bog, while expression of ammonium-producing genes was significantly higher in the bog compared to the palsa. Our findings highlight the release and rapid compositional shift of ON during thaw transitions. This underscores the need for further studies on thaw-released N to enhance models predicting N cycling and Arctic greenhouse gas emissions.